PENGARUH HIPOKSIA ISKEMIK PRENATAL TERHADAP GAMBARAN HISTOPATOLOGI GINJAL RATTUS NORVEGICUS GALUR SPRAGUE-DAWLEY - Mohammad Arief Adiatma (FKU 16 UMY 115, 2016)
Background: Hypoxia is a condition where body tissue does not get enough oxygen. Prenatal hypoxia is still a major cause of morbidity and mortality in developed and developing countries. Exposure of hypoxia during prenatal has a different impact on fetal development. Fetal hypoxia can impair fetal kidney development. Several studies have examined the effects of prenatal hypoxic-ischemic on kidney, but research of the effects of prenatal hypoxic-ischemic on renal histopathologic is still unclear. Methods: This study was experimental research with post-test control group design. Samples used in this study were the child of Rattus norvegicus Sprague-Dawley strain, that obtained from a pregnant rats who was induced by hypoxic-ischemic at different gestational age with the right uterine artery ligation. Pregnant rats divided into three groups, K is a control group who were not given the induction of hypoxic ischemic, P1 is a group that was given the induction of hypoxic-ischemic at 7 days of gestational age, and P2 is a group that was given the induction of hypoxic-ischemia at 11 days of gestational age. Samples used in this study were 7 rats child per group, which has fulfilled the inclusion and exclusion criteria. After the age of 35 days, all samples is conducted kidney organ harvesting and the kidneys tissue is being process with HE staining and histopathologic examination. The data were analyzed with Kruskal-Wallis and Mann-Whitney with significance level of 5%. Result: Group P1 has the highest amount kidney cells damage. Kruskal-Wallis test showed a significant difference with a p value of 0,000 (p<0,05). Post Hoc Mann Whitney test showed a significant differences in K-P1 with a p value of 0,01 (p<0,05) and K-P2 with a p value of 0,01 (p<0,05), whereas in P1-P2, have a differences, but not significant with a p value of 0,122 (p>0,05). Conclusion: There is a correlation between kidney histopathological changes of Rattus norvegicus Sprague-dawley strain with prenatal hypoxic-ischemic induction, the earlier induction is given then the greater the effect of hypoxia on renal toxicity.